Marchandiobasidium aurantiacum (Lasch) Diederich & Schultheis – новый для Украини вид лихенофильного гриба (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The locations, ecology and general distribution of the new for Ukraine lichenicolous fungus Marchandiobasidium aurantiacum (Lasch) Diederich & Schultheis are given in the article. The species is determined to be a parasite of the corticolous lichenes Physcia and Xanthoria.
Keywords: Marchandiobasidium aurantiacum, Kherson region, southern Ukraine.